Bacteraemia in Malawian neonates and young infants 2002–2007: a retrospective audit. Issue 3 (15th May 2012) - Gwee, Amanda; Coghlan, Benjamin; Everett, Dean; Chagoma, Newton; Phiri, Amos; Wilson, Lorna; Molyneux, Elizabeth
Abstract : Objectives: To assess the causes of bacteraemia in young infants and susceptibility to first-line antibiotics (benzylpenicillin plus gentamicin) at the Queen Elizabeth Central Hospital (QECH), Malawi during 2002–2007. Design: Retrospective analysis of demographic and microbiological data using laboratory records. Setting: QECH is Malawi's largest hospital with 7000 neonates admitted annually, 9% for septicaemia. Patients: All infants aged 60 days or less admitted to QECH that had a blood culture taken over the 6-year period. Main outcome measures: 6754 blood cultures were taken. 3323 organisms were isolated: one-third were pathogens, two-thirds contaminants. Gram-positive organisms (53%) were more common than gram-negatives (47%). Four organisms made up half of all pathogens: Staphylococcus aureus (15.3%), group B streptococci (13.5%), non-typhoidal salmonellae (12.6%) and Escherichia coli (10.5%). Apart from non-typhoidal salmonellae and Streptococcus pneumoniae, most organisms were more common in the first week of life than later. Overall, 28% of isolates during 2002–2007 were resistant to first-line antibiotic, higher than observed during 1996–2001 (22%). Penicillin susceptibility fluctuated while gram-negative resistance to gentamicin increased from 17% to 27% over the study period. Conclusions: In the QECH, pathogens causing young infant sepsis are an unusual mix of organisms seen in both developed and developing countries. Resistance to first-line antibiotics is higher than observed in most studies. Ongoing monitoring is needed and clinical outcome data would aid interpretation of findings. A high proportion of blood cultures were contaminated with skin flora—improved training and supervision of phlebotomists are needed to improve the utility of taking blood cultures.